Mental health teaching-learning process in Nursing graduation: a literature review (Research, Society and Development, 2020)
Mental Health Nursing has always been present throughout history, however it became more evident after the period of Psychiatric Reform in Brazil. There was an evolution in the treatment of patients with persistent and severe mental disorders, where, until then, assistance behaviors included inhuman and cruel methods, characterized by violence and abandonment. This is a bibliographic research with a qualitative approach, with the objective of describing the conduct of mental health education in undergraduate nursing courses for the training of nurses. After the association of all descriptors, 151 articles were found, 138 were excluded and 13 were selected. After the reflective reading, three categories emerged: The issue of madness and the legacy for Mental Health; The construction of the professional nurse and mental health and the nurse's duties in mental health. The training process of the nursing student in mental health needs to be sustained in the psychosocial paradigm in order to drive changes in the training of the future nurse. A study on the training of nursing students in mental health of HEIs in Brazil points out that their beliefs and motivations, in relation to the psychosocial assistance model, influence teaching and knowledge production. It is concluded that, specifically, emphasizing the process of academic training of professional nurses during graduation, a study that identifies and highlights academic behavior, as well as their respective expectations about the importance of teaching and learning content, becomes of great relevance. Mental Health.